SELECTION OF ANTAGONISTIC RHIZOBACTERIA POTENTIAL FOR BIOLOGICAL CONTROL OF Fusarium oxysporum - Anggit Cahyani; Harman Hamidson; Suwandi Suwandi; Abu Umayah (BIOVALENTIA: Biological Research Journal, 2023)
Fusarium oxysporum is a pathogen that causes wilt disease in many plants and can couse losses of up to fifty percent. Standard control is to use synthetic fungicides. However, continuous use of fungicides has a high environmental risk, so environmentally friendly and safe control efforts are needed. One way is by using rhizosphere bacteria or rhizobacteria. This research aims to obtain rhizobacteria isolates that can control the pathogen F. oxysporum, which causes fusarium wilt in vitro. This research was conducted from June to July 2023. The methods in this research included isolating rhizobacteria, observing the morphology of bacterial colonies, gram staining, gram reaction test, catalyst test, and in vitro antagonist test. Research data shows that of the thirty rhizobacteria isolates observed, all isolates had the potential to inhibit the growth of F. oxysporum. The KMTK2 showed the highest inhibitory ability isolate with an inhibitory ability of 73,99%, and the lowest inhibitory ability was shown by the TBA1 isolate with an inhibitory ability of 51,56%. Potential rhizobacteria isolates can suppress the growth of the pathogen F. oxysporum and can be used as a biological agent to reduce the use of pesticides in treating plant diseases.